Extended-Spectrum Beta-Lactamases Producing E. coli in Wildlife, yet Another Form of Environmental Pollution? - Guenther, Sebastian; Ewers, Christa; Wieler, Lothar H. (Frontiers in Microbiology, 2011)
Wildlife is normally not exposed to antimicrobial agents but can acquire antimicrobial resistant bacteria through contact with humans, domesticated animals and the environment, where water polluted with faeces seems to be the most important vector. E. coli, a ubiquitous commensal bacterial species colonizing the intestinal tract of mammals and birds, is also found in the environment. Extended-spectrum beta-lactamases producing E. coli (ESBL-E. coli) represent a major problem in human and veterinary medicine, particular in nosocomial infections. Additionally an onset of community acquired ESBL-E. coli infections and an emergence in livestock farming has been observed in recent years, suggesting a successful transmission as well as persistence of ESBL-E. coli strains outside clinical settings. Another parallel worldwide phenomenon is the spread of ESBL-E. coli into the environment beyond human and domesticated animal populations, and this seems to be directly influenced by antibiotic practice. This might be a collateral consequence of the community onset of ESBL-E. coli infections but can result (a) in a subsequent colonization of wild animal populations which can turn into an infectious source or even a reservoir of ESBL-E.coli, (b) in a contribution of wildlife to the spread and transmission of ESBL-E. coli into fragile environmental niches, (c) in new putative infection cycles between wildlife, domesticated animals and humans, and (d) in problems in the medical treatment of wildlife. This review aims to summarize the current knowledge on ESBL-E. coli in wildlife, in turn underlining the need for more large scale investigations, in particular sentinel studies to monitor the impact of multiresistant bacteria on wildlife.